Empowerment and burden: The effect of parents’ educational involvement, basic psychological needs satisfaction and academic stress - Quinto, Egdonna (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2024)
The study aimed to investigate the effect of parental involvement on basic psychological need satisfaction and academic stress. To deepen the concept of the study, literature was reviewed. The study used descriptive assessment and correlational research design. The population of the study was the senior high school students of the Divine Word College of Laoag. It used questionnaires to gather the data and inferential statistics were used to analyze the data specifically weighted mean and Analysis of Variance (ANOVA). The study found that overall, there is a significant correlation between parental involvement basic psychological need satisfaction and academic stress. In other words, parental involvement produces positive and negative outcomes at the same time. It can fulfil basic psychological needs satisfaction or improve well-being but at the same time, it can produce stress for the students. Looking into the specific findings, parent’s emotional involvement is associated with a basic psychological need for autonomy. The three components: emotional, cognitive and behavioral involvement affect the basic psychological need for competence. While emotional and cognitive involvement are associated with relatedness needs. The same is true with parents’ involvement with academic stress. Parent’s emotional involvement affects students’ level of stress in terms of external pressure and parents’ behavioural involvement significantly affects the students’ self-efficacy.